Black Theology and Pan-Africanism: An interconnected journey towards liberation - Dube, Zorodzai (Hervormde teologiese studies, 2025)
This article explores the intricate relationship between Black Theology and Pan-Africanism. The impetus behind this study is the resentment against the enduring legacy of historical oppression and the persistent sting of systemic discrimination experienced by individuals of African descent worldwide, as well as the perceived inadequacy of existing analytical frameworks to fully capture this complex phenomenon. As highlighted in this study, the greatest challenge for people of African descent is dehumanisation resulting from colonialism and racism, along with the ongoing struggle against neo-colonialism. The study is framed within the ideological concepts of Black Theology and Pan-Africanism, both of which advocate for the centrality of liberation, affirm the importance of identity and dignity, and emphasise the necessity of unity in overcoming oppressive structures. The article addresses the implicit research question of how these two paradigms intersect and contribute to the pursuit of liberation and self-determination. A major finding is the striking convergence of core tenets between Black Theology and Pan-Africanism, particularly their shared critique of oppressive power structures, their unwavering focus on liberation, and their emphasis on identity and self-respect as crucial elements of resistance.ContributionConsidering these findings, the study argues that merging Black Theology with Pan-Africanism offers a more comprehensive and powerful approach to addressing the intricate challenges of black freedom.